The efficiency of spermatogenesis and the support capacity of Sertoli cells in Characiformes - Rodrigues, Maira da Silva [UNESP]; Siqueira-Silva, Diógenes Henrique de; Quirino, Patrícia Postingel [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Elsevier, 2017)
This stereological analysis of the types of germ cells and the number of Sertoli cells per cyst in Astyanax altiparanae testes during spermatogenesis is the first such report in Characiformes. Testes of 25 male A. altiparanae were examined. Based on the number of spermatogonia B per cyst (469.2 ± 9.92), we estimated that spermatogonia undergo at least nine mitotic divisions before differentiating into primary spermatocytes. There are four spermatogonia types: undifferentiated spermatogonia A*, undifferentiated spermatogonia, differentiated spermatogonia, and type B spermatogonia. The number of Sertoli cells increased gradually from 1.41 ± 0.51 in the single undifferentiated spermatogonium A* to 9.25 ± 0.50 in cysts of spermatocytes in the leptotene/zygotene stage, possibly related to greater complexity of cellular events during the meiotic stage. The number of germ cells rose dramatically from spermatogonia A (1.0 ± 0) to spermatogonia B (469.2 ± 9.92); however, the quantity of spermatocytes inside the cysts in the leptotene/zygotene stage decreased (300.6 ± 6.97) relative to spermatogonia B, representing a loss of approximately 36% of the former number of cells. This was probably the result of apoptosis, which promotes successful development of the remaining cells during sperm production. The support capacity of Sertoli cells increased gradually during spermatogenesis.
Keywords: Fish reproduction; Germ cells; Spermatogenesis; Stereology; Testicular morphometry